2005
DOI: 10.1002/ppap.200400070
|View full text |Cite
|
Sign up to set email alerts
|

Surface Analysis of Plasma‐Deposited Polymer Films, 4

Abstract: Summary: XPS and NEXAFS spectroscopy were used for the chemical characterization of pulsed plasma‐deposited ethylene films before and after exposure to ambient air. The influence of external plasma parameters on the spectroscopic results was investigated. Information on the chemical character of the plasma‐polymerized films, such as the regularity of the primary structure, the amount of long‐living radicals, and branching or cross‐linking or both was derived from this data. “Irregularity” and radical concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
4
21
0
Order By: Relevance
“…Reference to the really fresh state of the films described in the previous section can be made. Principally, the aging phenomena of copolymer films investigated in this study are similar to these found with the respective plasma deposited homopolymers derived from the monomer that has a larger contribution to the chemical character of the copolymer film 27, 31, 33–35. The changes in surface chemistry during aging are investigated in terms of gains and losses in the relative surface content of oxygen and oxygen species as well, and losses in the unsaturated or aromatic character in relation to a variation of feed gas composition. …”
Section: Resultssupporting
confidence: 63%
“…Reference to the really fresh state of the films described in the previous section can be made. Principally, the aging phenomena of copolymer films investigated in this study are similar to these found with the respective plasma deposited homopolymers derived from the monomer that has a larger contribution to the chemical character of the copolymer film 27, 31, 33–35. The changes in surface chemistry during aging are investigated in terms of gains and losses in the relative surface content of oxygen and oxygen species as well, and losses in the unsaturated or aromatic character in relation to a variation of feed gas composition. …”
Section: Resultssupporting
confidence: 63%
“…Both effects are due to the fragmentation of the monomer in the plasma. With increasing DC, the energy input also increases, and therefore the degree of fragmentation and rearrangement of the monomer, resulting in a lower concentration of carboxylic groups and a higher concentration of radicals 21…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the peaks at 3030, 1605 and at 905 cm -1 could be attributed to the existence of vinyl groups in the deposited film [35,36]. Tibbit et al [37], Donohoe and Wydeven [38], Oran et al [39] and Swaraj et al [40] have pointed out that the plasma polymerization of ethylene yields a plasma-polyethylene polymer with different structural characteristics with respect to that obtained with conventional methods. The plasmapolyethylene polymer possesses chemical crosslinks, ramifications and unsaturated vinyl groups.…”
Section: Resultsmentioning
confidence: 99%